Development Study of T-Z Curve Generated from Kentledge System and Bidirectional Test - Nisa Utami Rachmayanti; Paulus Pramono Rahardjo (U Karst, 2021)
Pile loading tests to check the bearing capacity to support large loads. We can also use it to measure its deflection under lateral load.  There  are  two  tests:  the  axial  static  pile  load  test (Kentledge)  and  the  two-directional  static  pile  load  test (Bidirectional).  T-Z  curve  as  the  result  analysis  based  on  the instrumented  pile  test  data  describes  the  load  distribution  and mobilized skin friction along with the pile. Numbers of Vibrating Wire  Strain  Gauge  (VWSG)  mounted  in  several  depths  of  the bored  pile  and  two  tell-tale  on  top  and  toe  of  the  pile  used  as primary  data  in  this  research.  This  research  to  determine  the different  distribution  of  mobilized  skin  friction.  The  pile  from two different pile load test methods from the calculated t-z curve as  the  study  developed  from  both  methods  of  pile  test.  The research results that the kentledge system has bigger mobilized skin friction than in bidirectional test.